Metakognisi dan Gaya Berpikir: Membuka Potensi Pemecahan Masalah Fisika - Haeruddin; I Komang Werdhina; Muhammad Jarnawi; Syamsuriwal; Zuhdan Kun Prasetyo; Supahar (Postgraduate, University of Mataram, 2023)
Thinking styles and metacognition are related as they both have the same space in assessing one’s own abilities. Metacognition and thinking styles have an important role in unlocking the potential of physics problem solving. The objective of this study is to investigate the relationship between metacognition, thinking styles (particularly those proposed by Gregorc), and physics problem solving. The study involved a cohort of 364 students who were pursuing a physics degree at Tadulako University. The results indicated that metacognition behavior exhibited in the process of solving physics problems was classified as high category. The most dominant thinking style was abstract sequential, while the least was concrete random. The data analysis showed a significant difference in metacognition behavior between groups categorized by thinking style. Specifically, the concrete sequential (SK) group exhibited a significant difference with the abstract random (AA) group. These results provide further understanding of how metacognition and thinking styles play a role in physics problem solving. This study contributes significantly to comprehending the connection between metacognition, thinking styles, and the successful resolution of physics problems. The insights gained provide prospects for formulating more efficient physics learning methods that will ameliorate students' aptitude in tackling physics problems.